Anmisties and international Law from an historial perspective: Bartolomé de las Casas v. Hugo Grocio - Sánchez, Víctor M. (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
Any amnesty generates a conflict of values that is difficult to solve. What isthe “good” to prioritize in the circumstances that facilitate the proposal ofamnesties? Punishing the most serious crimes or to easy the restoration of peaceat the expense of the obligation of punishment? In Thought history there was acritical moment in the rationalization of the philosophical-legal ‘validity’ of theamnesty. Las Casas formulated the first theory about the conditional validityof amnesties based on his theory of the ‘social pact’. A century later Grotiusresponded with the ‘eminent domain’ theory of the sovereign who affirmedthe validity of any amnesty fixed in treaties because of its public utility. Thegrotian position prevailed until the end of s. XX.
Keywords: amnesty; social pact; eminent domain; international Law